Mesenchymal stem cell-derived exosomes as a plausible immunomodulatory therapeutic tool for inflammatory diseases - Zubair, Muhammad; Abouelnazar, Fatma A.; Iqbal, Muhammad Asad; Pan, Jingyun; Zheng, Xuwen; Chen, Tao; Shen, Wenming; Yin, Jinnan; Yan, Yongmin; Liu, Pengjun; Mao, Fei; Chu, Ying (Frontiers in Cell and Developmental Biology, 2025)
Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs), especially, exosomes are considered to have diverse therapeutic effects for various significant diseases. MSC-derived exosomes (MSCex) offer substantial advantages over MSCs due to their long-term preservation, stability, absence of nuclei and fewer adverse effects such as infusion toxicity, thereby paving the way towards regenerative medicine and cell-free therapeutics. These exosomes harbor several cellular contents such as DNA, RNA, lipids, metabolites, and proteins, facilitating drug delivery and intercellular communication. MSCex have the ability to immunomodulate and trigger the anti-inflammatory process hence, playing a key role in alleviating inflammation and enhancing tissue regeneration. In this review, we addressed the anti-inflammatory effects of MSCex and the underlying immunomodulatory pathways. Moreover, we discussed the recent updates on MSCex in treating specific inflammatory diseases, including arthritis, inflammatory bowel disease, inflammatory eye diseases, and respiratory diseases such as asthma and acute respiratory distress syndrome (ARDS), as well as neurodegenerative and cardiac diseases. Finally, we highlighted the challenges in using MSCex as the successful therapeutic tool and discussed future perspectives.